Madurese Local Wisdom-Based Audiovisual Media For Enhancing Listening Skills In 5-6 Year Old - Hofifi, Moh. Nurul; Reswari, Ardhana (Aulad: Journal on Early Childhood, 2026)
Early childhood listening skills need to be developed through media that is contextual to the socio-cultural environment. This study aims to explore the use of audio-visual media based on Madurese local wisdom to develop the listening skills of 5-6 year old children. This descriptive qualitative study involved 43 children, 2 classroom teachers, and the principal of RA Al Munawarah Jungcangcang Pamekasan as informants. Data were collected through participatory observation, in-depth interviews, and documentation, and analyzed using the Miles and Huberman model. The results showed that audio-visual media containing Madurese folk tales, traditional songs, and traditional clothing improved children's focus, understanding of information, memory, and active participation. Implementation constraints included limited local content, technical problems, language barriers, and classroom management, which were overcome through content development and scaffolding reinforcement. The integration of local wisdom in audio-visual media effectively developed listening skills while strengthening children's cultural identity. Implications included the development of a digital repository of local content and the strengthening of teachers' technological-pedagogical competencies.